Analysis of Compatibility Test of Mesona Palustris (Black Grass Jelly) and Chitosan Solution on Formation Water Saltity - Mohamad Obby Adianto; Muhammad Agni Gustama; Ferdian Budi Ar-Rouf (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
The primary purpose of polymer injection is to reduce the water-oil mobility ratio. Commonly used polymers are polyacrylamide and polysaccharides. By increasing the viscosity of the injection fluid, polymer injection can improve sweep efficiency, thereby increasing oil recovery. Petroleum refining relies heavily on macroscopic and microscopic compression efficiency. This study aims to determine the compatibility test results between mesonapalustris and chitosan to determine whether good compatibility test results are obtained. The method used in this study is a laboratory experiment with observation. Compatibility was evaluated based on visual observation and qualitative stability indicators, with no effect across all salinity and concentration ranges. Quantitative indicators showed viscosity retention of >90% at and temperature. This demonstrates the potential of biopolymers as alternative agents in polymer flooding, with an increase in oil recovery of 15–20% OOIP.  Compatibility testing of polymer solutions in formation water is carried out to determine whether the polymer solution is completely soluble in the formation water. The test is carried out by dissolving the polymer in formation water with salinities of 10,000, 15,000, and 20,000 mg/L and polymer concentrations of 500, 1,000, and 2,000 mg/L. The solution is then placed in a bottle and observed for complete dissolution or sedimentation. Based on the results and discussions, experimental laboratory testing of black seaweed jelly and chitosan revealed compatibility results, which showed that all polymer solutions, both black seaweed jelly and chitosan, were compatible with various salinities of formation water, indicating that all polymer solutions were completely dissolved, no precipitation occurred and this suggests potential applicability of biopolymers as alternative agents in polymer flooding.